Isolation and Characterization of Antibiotic Resistant Bacteria from Swiftlet Feces in Swiftlet Farm Houses in Sarawak, Malaysia - LEONG SUI SIEN; SAMUEL LIHAN; LING TECK YEE; CHIA HWA CHUAN; LIM CHAN KOON (Microbiology Indonesia, 2013)
There is a growing concern on the occurrence of antimicrobial resistance. Development of multiple antibiotic resistant bacteria has overtaken new drug development and threatened the patients with untreatable infections. This study was conducted to isolate and characterize the antibiotic resistant bacteria from swiftlet farm houses located in various places including Kota Samarahan, Semarang, Saratok, Betong, Sarikei, Sibu, Sepinang, Maludam, Miri, and Kuching in Sarawak, Malaysia. Five feces samples were collected randomly from each site. One gram of the feces sample was diluted in 9 mL of 0.85% normal saline solution. The diluted sample was plated on Trypticase Soy agar plates and incubated at 37±1 °C for 24 h. A total of 500 bacteria isolates were then identified using 16S rRNA analysis method. Disc diffusion method was then used to confirm the resistant phenotypes of these isolates. The results showed that the means of the bacterial colony count were significantly different (p<0.05) from one another, with the highest log CFU g-1 (9.22±0.72) found in Kota Samarahan and the log10 lowest log CFU g-1 (6.03±0.62) in Betong. Besides, the isolated bacteria were identified as 96% Gram positive log10 bacteria and 4% Gram negative bacteria. The isolated bacteria were highly resistant to penicillin G (36.80±23.87%), ampicillin (28.60±17.13%), and rifampicin (16.90±13.70%). Thus, swiftlet feces are good reservoir for a range of antibiotic resistant bacteria which may pose a potential health hazard to human.